Organizational Citizenship Behavior on Nurses : The Role of Organizational Climate and Commitment - Adnans, Abdhy Aulia; Hadiyani, Sherry; Zahreni, Siti; Fahmi, Fahmi (LPPM Universitas Terbuka, 2021)
Abstract Hospitals in organizing excellent quality health services require human resources committed to the organization and a positive and conducive organizational climate. This study aims to determine the effect of organizational climate and organizational commitment to organizational citizenship behavior of nurses at USU Hospital. In this study, there are two independent variables: organizational climate and organizational commitment, and one dependent variable: organizational citizenship behavior. This research is quantitative research conducted using samples from the population of nurses at USU Hospital, where a sample of 125 nurses was obtained. The data analysis method used in this study is a statistical analysis with multiple regression analysis methods. Findings. The result of this study indicates a simultaneous influence between organizational climate and organizational commitment to organizational citizenship behavior.